2016
DOI: 10.1007/s00253-016-7654-x
|View full text |Cite
|
Sign up to set email alerts
|

Altered susceptibility to the bactericidal effect of photocatalytic oxidation by TiO2 is related to colistin resistance development in Acinetobacter baumannii

Abstract: Multidrug-resistant Acinetobacter baumannii is a well-documented pathogen associated with hospital-acquired infections. In addition to multidrug resistance, A. baumannii can also become resistant to colistin, the antibiotic treatment of last resort, by the loss of the lipopolysaccharide from its outer membrane. Here, we demonstrate that the development of colistin resistance also increases the resistance of A. baumannii to titanium dioxide (TiO2) photocatalysis. Both colistin-sensitive A. baumannii (CSAB) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…The evolution of cells to become CRAB, in contrast to CSAB, resulted in the complete loss of LPS production . Our previous study also confirmed the difference in LPS protein levels in CSAB and CRAB by two‐dimensional gel electrophoresis . In general, LPSs stabilize a bacterium's structure by acting as a protective impermeable barrier; however, lipid A of the LPS may be the specific target responsible for the lipid peroxidation of colistin.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…The evolution of cells to become CRAB, in contrast to CSAB, resulted in the complete loss of LPS production . Our previous study also confirmed the difference in LPS protein levels in CSAB and CRAB by two‐dimensional gel electrophoresis . In general, LPSs stabilize a bacterium's structure by acting as a protective impermeable barrier; however, lipid A of the LPS may be the specific target responsible for the lipid peroxidation of colistin.…”
Section: Discussionsupporting
confidence: 76%
“…The minimum inhibitory concentration (MIC) of colistin for the CRAB strain in this study was 32 μg/mL. We have used this CRAB strain for a bioaerosol study and TiO 2 susceptibility tests …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations